Synthesis of Sebacic Acid Using a De Novo Designed Retro‐Aldolase as a Key Catalyst. Issue 8 (6th April 2017) - Otte, Konrad B.; Maurer, Elena; Kirtz, Marko; Grabs, Daniela; Althoff, Eric; Bartsch, Sebastian; Vogel, Andreas; Nestl, Bettina M.; Hauer, Bernhard
Abstract: The production of new organic compounds from natural feedstocks drives the construction of new biosynthetic cascades. To develop and generate valuable complex chemicals, it is necessary to go beyond natural enzymes towards de novo designed and engineered variants for both natural and non‐natural compounds. Herein, we exploit the applicability of a de novo retro‐aldolase for the synthesis of sebacic acid, a valuable precursor for bio‐based polymers. From ricinoleic acid, a route composed of four individual enzyme‐catalyzed steps was developed. As a result of the narrow substrate scope of natural aldolases, this enzymatic route could only be realized by the design and engineering of a de novo retro‐aldolase. We further highlight the outstanding potential of this technology for the realization of non‐natural reactions and pathways. Abstract : Going retro : We apply the principles of "biocatalytic retrosynthesis" to the synthesis of the medium‐chain α, ω‐dicarboxylic acid sebacic acid using a de novo designed and engineered retro‐aldolase for a key biocatalytic step.